Kesiapsiagaan Individu dalam Menghadapi Bencana Gempa Bumi di Institusi Pendidikan Tinggi: Analisis Deskriptif - Silamma, Kalvari; Sri Sahayati (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
Introdution: The Special Region of Yogyakarta, particularly Sleman Regency, is an area with a high earthquake threat. The Faculty of Health Sciences (FIKES) at Respati University of Yogyakarta is located in this high-risk zone, making disaster preparedness among educational staff crucial. This study aims to illustrate earthquake disaster preparedness among lecturers, educational staff, and general staff at FIKES UNRIYO. Research Methods: The research adopts a Cross-Sectional design with a sample of 90 respondents selected through simple random sampling. Data were collected using the LIPI/UNESCO (2006) questionnaire, which evaluates preparedness based on knowledge, emergency response plans, warning systems, and resource mobilization. The data were analyzed descriptively. Results: The findings indicate that the respondents' preparedness index is 82%, categorized as high. Conclusion: Lecturers, educational staff, and general staff at FIKES UNRIYO demonstrate a high level of earthquake disaster preparedness, although some parameters still require optimization